2018
DOI: 10.1038/s41419-017-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Chir99021 and Valproic acid reduce the proliferative advantage of Apc mutant cells

Abstract: More than 90% of colorectal cancers carry mutations in Apc that drive tumourigenesis. A 'just-right' signalling model proposes that Apc mutations stimulate optimal, but not excessive Wnt signalling, resulting in a growth advantage of Apc mutant over wild-type cells. Reversal of this growth advantage constitutes a potential therapeutic approach. We utilised intestinal organoids to compare the growth of Apc mutant and wild-type cells. Organoids derived from ApcMin/+ mice recapitulate stages of intestinal polypos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Furthermore, butyrate also enhances the barrier function of intestinal epithelial cells by up-regulating TJ protein claudin-1 (27). As HDAC inhibitors, butyrate, and valproic acid are important for maintaining stem cell populations, and stimulating normal cell growth in small intestinal organoid culture (13,28). SCFAs also induce different effects on immune cells in a cell-and environment-specific context.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, butyrate also enhances the barrier function of intestinal epithelial cells by up-regulating TJ protein claudin-1 (27). As HDAC inhibitors, butyrate, and valproic acid are important for maintaining stem cell populations, and stimulating normal cell growth in small intestinal organoid culture (13,28). SCFAs also induce different effects on immune cells in a cell-and environment-specific context.…”
Section: Disscussionmentioning
confidence: 99%
“…Both epithelial HDAC1 and HDAC2 contribute to regulation of the intestinal inflammatory response by regulating intestinal epithelial cell proliferation and differentiation (42). The HDAC inhibitor valproic acid is commonly used with GSK-3 inhibitor Chiron99021 in early passages for organoid culture to improve the efficiency of organoid formation because they can up-regulate Wnt and Notch signaling, resulting in the presence of more Lgr5+ stem cells (13,28). Interestingly, Langlands et al found that the combination of valproic acid and Chiron99021 restricts the growth advantage of Apc mutant (mutations in Adenomatous polyposis coli) organoid cells while stimulating the growth of wild-type cells, implying that HDAC inhibitors selectively protect the normal crypt stem cells in the intestine (28).…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organoids initially displayed budding and were indistinguishable from healthy organoids, but spontaneously developed cystic morphology after several passages. This was congruent to the loss of heterozygosity of the APC gene 198,199 , correlating with the adenoma stage in vivo. I the adenoma stage in intestinal cancer.…”
Section: Repression Of Tcf7l2 Rescues Cystic Apc Min/small Intestine supporting
confidence: 58%
“…Since IL-22 has been implicated in promoting stemness and proliferation in colorectal cancer cell lines (Kryczek et al, 2014;Kirchberger et al, 2013;Lindemans et al, 2015), we asked how transformed SI epithelial cells responded to IL-22. We treated transformed Apc Min/Min SI organoids (Langlands et al, 2018) derived from Apc Min/+ mice with and performed RNASeq. In contrast to WT cells, we found only a minute number of genes regulated by IL-22…”
Section: Defective Il-22 Mediated Gene Regulation In Apc-mutant Iecmentioning
confidence: 99%